SURFACE COMPLEXATION OF PB(II) AT OXIDE-WATER INTERFACES: II. XAFS AND BOND-VALENCE DETERMINATION OF MONONUCLEAR PB(II) SORPTION PRODUCTS AND SURFACE FUNCTIONAL GROUPS ON IRON OXIDES - Bargar J.R.; Brown G.E.; Parks G.A. (My University, 1997)
Pb(II) sorption on goethite and hematite powders was studied at room temperature as a function of pH (6-8), sorption density (2-10 μmoles/m2), and [Pb]eq (0.2 μM - 1.2 mM) in 0.1 M NaNO3 electrolyte using XAFS spectroscopy. Pb(II) ions were found to be hydrolyzed and adsorbed as mononuclear bidentate complexes to edges of FeO6 octahedra on both goethite and hematite under all conditions. Hydrolysis of Pb(II) appears to be a primary source of proton release associated with surface complexation of Pb(II). A bond-valence model was used to relate the relative stabilities of iron-oxide surface functional groups and Pb(II) adsorption complexes to their structures and compositions. This combined approach suggests that Pb(II) adsorption occurs primarily at unprotonated [FeFeFe???O-12] sites and at [Fe-OH+122] sites. Several adsorption reactions are proposed. Comparison to EXAFS results from Pb(II) adsorption on aluminum oxides suggests that the edge lengths of surface AlO6 or FeO6 octahedra partially determine the reactivities and densities of available surface sites. The results of this study provide a basis for constructing chemically realistic descriptions of Pb(II) surface complexation reactions on Fe (hydr) oxides.